Snow Whiteâ€™s Characterizations in â€œSnow White and The Seven Dwarfsâ€ Vera Southgateâ€™s and Regis Maineâ€™s Versions - Made Ari Arthawati (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This study aims to 1) Describe and compare the characterizations of Snow White in the short story Snow White and The Seven Dwarfs by Vera Southgate and the comic Snow White and The Seven Dwarfs by Regis Maine; and 2) Elaborate how the characterizations of Snow White impacts the plot of Snow White and The Seven Dwarfs short story â€œSnow White and The Seven Dwarfsâ€ in Vera Southgateâ€™s and Regis Maineâ€™s versions. By utilizing close reading analysis, it is found that Snow White in Snow White and The Seven Dwarfs by in Vera Southgate version is presented as a beautiful, kind-hearted, and stubborn, naive, and weak princess. But, in Regis Maine version, Snow White is presented as a beautiful princess with a lot of good personalities, such as cheerful, well-mannered, and loyal/ faithful, hardworking, honest, friendly/ communicative, religious, social caring, nature-loving, tolerant, peace-loving, appreciative, and responsible. Those characterizations have an impact to the plot of the story. The more characterizations in Snow White, the more complex the plot of the story will go on. Thus, if there is a change or addition in the characterization of the main character, it will change the plot of the story.